2022
DOI: 10.1039/d1fo03026d
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside CK ameliorates hepatic lipid accumulation via activating the LKB1/AMPK pathway in vitro and in vivo

Abstract: Nonalcoholic fatty liver disease (NAFLD) is a metabolic liver disease with complex etiology, which is considered as one of the main causes of hepatocellular carcinoma (HCC). The incidence of NAFLD...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 44 publications
0
22
0
1
Order By: Relevance
“…First, in hepatocytes, Panax ginseng treatment suppressed NAFLD-induced cellular stress responses, such as oxidative stress [ 23 , 50 ], ER stress [ 35 , 47 ], and mitochondrial dysfunction [ 26 ]. In addition, the administration of Panax ginseng has beneficial effects on hepatic energy metabolism by activating AMP-activated protein kinase [ 22 , 29 , 56 , 58 ] but inhibiting the mammalian target of rapamycin complex 1 [ 37 ], resulting in the normalization of hepatic glucose [ 30 ] and lipid metabolism [ 32 , 33 , 34 , 41 ] in NAFLD. In the hepatic microenvironment, Panax ginseng reduced inflammatory responses by preventing activation of the NLR family pyrin domain containing 3 (NLRP3) inflammasome and nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB), thereby suppressing gene and protein expression levels of interleukin (IL)-1β, IL-6, and tumor necrosis factor-α [ 35 , 36 , 38 , 49 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, in hepatocytes, Panax ginseng treatment suppressed NAFLD-induced cellular stress responses, such as oxidative stress [ 23 , 50 ], ER stress [ 35 , 47 ], and mitochondrial dysfunction [ 26 ]. In addition, the administration of Panax ginseng has beneficial effects on hepatic energy metabolism by activating AMP-activated protein kinase [ 22 , 29 , 56 , 58 ] but inhibiting the mammalian target of rapamycin complex 1 [ 37 ], resulting in the normalization of hepatic glucose [ 30 ] and lipid metabolism [ 32 , 33 , 34 , 41 ] in NAFLD. In the hepatic microenvironment, Panax ginseng reduced inflammatory responses by preventing activation of the NLR family pyrin domain containing 3 (NLRP3) inflammasome and nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB), thereby suppressing gene and protein expression levels of interleukin (IL)-1β, IL-6, and tumor necrosis factor-α [ 35 , 36 , 38 , 49 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…( A ) A graph of the risk in the bias of included studies. ( B ) A summary of the risk of bias in the included studies [ 7 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ].…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The typical metabolization model of ginsenosides to compound K (CK) has been widely reported ( Figure 5 ), with enhanced anti-tumor, anti-inflammatory, and lipid-lowering effects ( Kim et al, 2013 ; Kim, 2018 ). At 50 μM, CK inhibits the growth of glioblastoma cells by upregulating caspase-3-, caspase-8-, caspase-9- and cAMP-dependent protein kinases ( Lee et al, 2017 ); At 20 μM, CK reduces hepatic lipid accumulation in human hepatocellular carcinoma cells by activating AMPK ( Zhang et al, 2022 ); CK attenuates macrophage inflammation and foam cell formation via autophagy induction and by modulating NF-κB, p38 and JNK/MAPK signaling ( Lu et al, 2020 ). The bioavailability of curcumin metabolites is dependent on the microbiota dependent ( Hassaninasab et al, 2011 ).…”
Section: Biotransformation Contributions To Mining the Active Substan...mentioning
confidence: 99%
“…Non-alcoholic fatty liver disease (NAFLD) is a metabolic liver disease with complex etiology and is considered one of the major causes of HCC development. Zhang et al ( Zhang J et al, 2022 ) observed that ginsenoside C-K reduced lipid deposition in HepG2 cells, attenuated lipid accumulation in serum and liver tissues, ameliorated liver inflammation and injury, regulated the expression of factors related to lipid synthesis and metabolism, activated the phosphorylation of LKB1 and AMPK, and intervened in the progression of NAFLD. In addition, Li et al ( Li et al, 2022a ) observed that GRg1 significantly downregulated the expression level of sphingosine-1-phosphate lyase 1 (SGPL1) and increased the expression levels of p-Akt and p-ERK1/2 in steatosis HHL 5 cells, exerting an anti-apoptotic effect on nonalcoholic fatty liver cells.…”
Section: Prevention Of Precancerous Lesions By the Active Ingredients...mentioning
confidence: 99%